Exploring perceptions of Portuguese police about human trafficking victims and perpetrators - Cunha, Ana Paula Morais Pinto da (Crime, law and social change, 2022)
The present study uses a qualitative approach to explore how Portuguese police perceive human trafficking and the individuals involved. Three hundred and twenty-five professionals (aged 21-54) completed an online survey about human trafficking. The resulting data suggest that Portuguese police have a narrative congruent with the European image of the "iconic" victim and trafficker, which is usually framed by the mass media. In a country such as Portugal, where there are a significant number of labor trafficking cases, those stereotyped narratives may narrow the efforts and the interventions of police officers. However, this study also suggests a similarity between the data reported about the forms of recruitment, exploitation, and control recognized by the Portuguese police and the literature available. This study has important implications for practitioners and highlights the need to invest in empirical research to produce efficient policies and interventions.